Localization and tracking of players using multiple cameras - Saludares, Maria Isabel S. (Institute of Physics, College of Science, University of the Philippines Diliman, 2015)
We propose to develop a tracking system with a novel approach for localization and tracking of multiple players using several static cameras. We use the localized track of the player and project it to its corresponding top view for visualization. Image segmentation techniques, camera calibration, and clustering were used to develop the tracking system. The system was applied to: controlled set-up and soccer game.